The People Shall Not Dwell Alone: The Hebrew Bible in Light of Chinese Classics - Lupeng Li (Religions)
This article compares the similar texts in historiography, legend, poetry, and law between the Hebrew Bible and Chinese classic works, emphasizing the mutual reflection and illumination of the two in terms of culture. This article holds that a literary work, just like an object, will release a certain form of energy, which will have an impact on other works and, at the same time, be influenced by other works. This article examines Chinese classic works from the perspective of the Hebrew Bible to gain new insights. By discussing the traditional comparative methods in biblical studies, the article emphasizes the possibility of comparison between different cultures. It is believed that, for similar stories and texts, it is important to analyze their specific cultural backgrounds and writing environments and to reveal the deep-seated reasons in terms of philosophy, history, society, culture, personal life experiences, etc., behind the phenomena of similarities and differences. Using this method, the article deeply analyzes the similarities and differences between the two kinds of texts in specific literary genres such as historiography, poetry, and law and gives examples to illustrate the similarities and differences between these two types of literary works. The study of these narratives within a comparative framework enables people to have a deeper understanding of these texts and the societies that produced them, while also respecting the unique backgrounds and meanings of each work. The article underlines the significance of cross-cultural comparison in the studies of the Bible and Chinese classic works. This research approach, as proposed, enriches the comprehension of these two literary traditions and their profound influence on the shaping of human history and culture.